Efektivitas Story Box Game Berbasis Deep Learning terhadap Keterampilan Komunikasi Anak Usia 5-6 Tahun - Mutmainna Mutmainna; Intisari Intisari; Nur Alim Amri (Jurnal Ilmiah POTENSIA, 2026)
The low communication skills of early childhood children in constructing sentences, responding to questions, and expressing ideas orally became the background of this study. This research aims to examine the effectiveness of the Story Box Game media based on deep learning on the communication skills of children aged 5-6 years at TK Jannatul Firdaus Makassar. This study employed an experimental method with a one-group pretest-posttest design involving 15 children as research subjects. Data were collected through observation instruments and analyzed using descriptive statistics, the Wilcoxon Signed Rank test, and N-Gain analysis. The results showed that the implementation of the Story Box Game based on deep learning had a significant effect on children’s communication skills. The Wilcoxon Signed Rank test results indicated a value of Z = -3.487 with Asymp. Sig. (2-tailed) < 0.001. Furthermore, the N-Gain analysis result was 0.55, which falls into the medium category. The improvement in communication skills was reflected in children’s increased confidence in speaking, better coherence in expressing ideas, and richer vocabulary usage. Therefore, the Story Box Game media based on deep learning is effective in improving early childhood communication skills